Enhanced UV–Visible photocatalytic activity of Cu-doped ZnO/TiO2 nanoparticles - Delsouz Khaki, Mohammad Reza; Shafeeyan, Mohammad Saleh; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan (Springer, 2018)
Cu–ZnO/TiO2 nanoparticles were prepared by entrapping copper ions into crystalline matrix of ZnO/TiO2 through sol–gel synthesis method. The photocatalyst matrix loaded with different copper concentrations was calcined at 500 and 700 °C. Thermal property, crystalline structure, surface morphology and absorption spectra of Cu–ZnO/TiO2 were characterized by thermogravimetric analysis, X-ray diffraction, scanning electron microscopy, transmission electron microscope and UV–Vis spectrophotometry. Besides, its specific surface area and band gap energy level were estimated through BET surface area method, Kubelka–Munk model and Planck’s equation. The results revealed that Cu–ZnO/TiO2 had a more thermally stable lattice compared to TiO2/ZnO and hence the phase transformation from anatase to rutile is retarded under higher calcination temperature in Cu–ZnO/TiO2 lattice. The photoactivity of Cu–ZnO/TiO2 was then evaluated through degradation of methyl orange under visible light irradiation. Among different samples, the samples that were calcined at 500 °C exhibited the highest photocactivity compared to those calcined at 700 °C. Cu–ZnO/TiO2 with a Cu content of 3 wt% was observed to have the maximum activity, giving C/C0 value of 0.03 after 150 min. This value was about 12 and 28.3 times higher than that of ZnO/TiO2 and TiO2, respectively.